Plant trait diversity buffers soil moisture dynamics on coastal dikes during drought periods - Jan-Michael Schönebeck; Dorothea Bunzel; Maike Paul; Torsten Schlurmann (PLoS ONE, 2026)
Soil moisture is considered a key component for the structural integrity of engineered ecosystems, such as sea dikes. Although plants are important determinants of physical soil properties in dike greening, research lacks on the extent to which greater biodiversity can mitigate soil moisture loss during extreme weather events. This provided the motivation to investigate the influence of two plant communities of different species composition – namely, an herb-dominated vegetation area (‘Mix-Herb’) compared to a grass-dominated area (‘Mix-Grass’) – on soil physical conditions over the course of one year on a summer dike in northern Germany. Vegetation mapping, high-resolution measurements of soil temperature and moisture, and comprehensive precipitation data provided the framework for the investigations. It was found that species diversity (Shannon Index) declined over time from 2.7 to 2.3 for ‘Mix-Herb’ and from 2.2 to 2.0 for ‘Mix-Grass’. In-situ measurements of soil physical conditions revealed that the ‘Mix-Herb’ plant community moderated diurnal soil temperature variations more effectively than ‘Mix-Grass’. During a drought in June 2023, the ‘Mix-Herb’ vegetation area was also considerably less affected by soil heating and moisture deficit. However, after mowing, the thermal buffer effect reversed and greater diurnal temperature variations occurred in the soils of the herbaceous vegetation. During a second drought in September 2023, the’Mix-Grass‘soils exhibited higher moisture loss rates after mowing. These findings highlight the importance of the functional composition of plant communities and management practices such as mowing schedules, tailored spatially and temporally to ecological and climatic conditions, for regulating the soil microclimate on dike systems, with potential implications for dike’s resistance under climatic extremes.